I International scientific conference "Protected steppesof Ukraine. The state and prospects of their saving" (September, 18-22 2007, Askania-Nova, Ukraine) (CHORNOMORSKI BOTANICAL JOURNAL, 2007)
I International scientific conference "Protected steppesof Ukraine. The state and prospects of their saving" (September, 18-22 2007, Askania-Nova, Ukraine)